Effect of oxide-ion conductivity of apatite-type Ln10Si6O27 on catalytic activity for toluene combustion - Kenji Matsuo (Taylor & Francis Group, 2021)
By using apatite-type Ln10Si6O27 (Ln = La, Sm, Gd) solids with oxide-ion-conduction properties, the effect of conductivity on the catalytic activity of 1 wt% Pt/Ln10Si6O27 for toluene combustion was clarified. With increasing Ln3+ ion size, the lattice volume of Ln10Si6O27 increased, resulting in the enhancement of the conductivity, likely due to the expansion of the oxide-ion-conducting pathway; that is, the conductivity increased in the order Gd10Si6O27 < Sm10Si6O27 < La10Si6O27. The conductivity of the Ln10Si6O27 promoter affected the oxygen release ability of 1 wt% Pt/Ln10Si6O27, which led to the oxidation of Pt0 to Pt2+/4+. Correspondingly, the Pt/Ln10Si6O27 catalyst facilitated toluene combustion, and the catalytic activity increased in the order 1 wt% Pt/Gd10Si6O27 < 1 wt% Pt/Sm10Si6O27 < 1 wt% Pt/La10Si6O27; this order was not consistent with the surface area, Pt dispersion, or acidity. These results indicate that the catalytic activity was affected by the conductivity of the Ln10Si6O27 promoter.